Genotypic x environment interaction on yield and quality traits of asiatic cotton (Gossypium arboreum) - TUTEJA, O P; SINGH, D P; CHHABRA, B S (The Indian Journal of Agricultural Sciences, 2013)
An investigation was conducted to study the stllbility parameters with 30 genetic male sterility based hybrids ofasiatic cotton (Gossypium arboreum L.) and standard check 'DS 5' were grown at 2 locations with 3 level of spacingsin order to provide 6 contrasting environments. The observations were recorded on seed cotton yield and quality traits.Variances due to genotypes, environments and G x E interaction were significant for all the traits studied. Both linearand non-linear components were important for seed index, ginning out turn, fibre fineness and maturity coefficient,whereas non-linear component was predominant for seed cotton yield, 2.5% span length, lint index and bundle strength.Simultaneous consideration of all the parameters of stability revealed that the hybrids 'DS 5' X 'HD 266', 'DS 5' X 'HD273', 'DS 5' X 'HD 305' and 'DS 5' X 'Climiniless 'J.' were found stable for yield of seed cotton yield but unstable formost of the quality traits. The hybrids 'DS 5' X 'PR 51' was stable for most of the quality traits under study.